Penerapan Model Pembelajaran Problem-Based Learning dengan Metode Debat terhadap Keterampilan Bertanya Mahasiswa Mata Kuliah Ilmu Kealaman Dasar Universitas Muhammadiyah Palangkaraya - Nurul Hikmah Kartini (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
This study uses a quasi-experimental design that aims to measure students' questioning skills through the application of Problem-Based Learning (PBL) model with Debate method, which is specifically the purpose of the research as follows: 1) describe the skills of inquiring, and 2) describe the implementation of learning. The population in this study is the third-semester students who take Basic Basic Science courses in the odd semester of academic year 2017/2018. The sample of this research is the students of State Administration study program which amounted to 35 people as control class using PBL model, and PGSD study program which amounted to 38 people as a class of actor using PBL model with the method of debate. Sample determination is determined purposively. Question skill data will be analyzed descriptively after being tabulated with criteria of excellent, good, medium, low, very low. The results showed that students' questioning skills with the PBL model using the debate method experienced a higher number of emerging than the control class. Details of the results are from 10 criteria of questions, the dominant emerging is criterion 3 is the question that arises logically from the observations made with the number 25%, criterion 6 is the question of analyzing the observations with the number 25%, and criterion 8 is the question leads to reasonable predictions with a 50%.